ANALYSIS OF THE QUALITY OF CIVIL SERVANTS AND THE PERFORMANCE OF CIVIL SERVANTS AT THE SERVICE OF POPULATION AND CIVIL REGISTRATION IN BONE BOLANGO DISTRICT - Isti Alawiyah Ishak; Djamila Podungge; Nuzmerini Rauf (Journal of Economic, Business, and Administration (JEBA), 2023)
The purpose of this study was to find out how the quality and performance of Civil Servants at the Population and Civil Registration Office of Bone Bolango Regency. The method in this study uses descriptive qualitative methods with observational data collection techniques, in-depth interviews and documentation. The results of the study show that 1) The performance of civil servants in the service of the Population and Civil Registration Service in 2016-2021 in the service of population documents has greatly increased, both in terms of ownership of Identity Cards, Family Cards, birth certificates, Child Identity Cards and Death Certificates and Indexes Community Satisfaction (IKM). However, in terms of completing service tasks in managing various paperwork such as making ownership of an Identity Card or Family Card, the NIK is out of sync with the date, month and year of birth of the population. In terms of the quality of employees, the population and civil registration service for Bone Bolango Regency still has deficiencies, namely the problem of timeliness, for time discipline carried out by civil servants for the population and civil registration service for Bone Bolango Regency there are still several employees who violate these regulations. 2) In accordance with the results of interviews with researchers with informants at the Dukcapil Office, in improving performance and quality, the Head of Service strongly urges employees to take part in Bimtek, Training and Workshops in order to motivate and increase competence for regional apparatus for service improvement. Not only that, as a form of appreciation the head of the service gives rewards to employees who excel or who successfully complete their duties properly.